Analysis of mechanisms for stimulating the development of small distributed generation on the side of household consumer in market conditions - Pustovij, A.; Veremiichuk, Y. (Energy and Automation, 2025)
The paper studies the mechanisms for stimulating the development of electricity production from renewable energy sources on a market basis. An analysis of legal, organizational and economic incentives implemented by the state for consumers with their own generation is carried out. Schemes of interaction between electricity market entities are presented and available formats for the operation of generation on the household consumer side are studied with a comparative analysis. During the study, the entities and the nature of the influence are determined in accordance with each presented interaction model. The models are assessed for risks that may arise from household active consumers. It was established that for the further development of the reliability of the electricity supply system and increasing the efficiency of existing models of low-power consumers, it is necessary to harmonize approaches to the implementation of photovoltaic plants with European regulatory requirements. A vision of ways to improve legal regulation to increase the attractiveness of the interaction of active household consumers with the electricity market and improve the technical mutual influences of the power system has been further developed. Key words: active consumer, household consumer, self-production, self-consumption, green tariff, generation, renewable energy sources